Life in the Deserts - Baker, Lucy, 1964-; Mosley, Francis; McBride, Valerie (New York : F. Watts, 1990)
Describes the desert environment and the different types of plants and animals that live there.
Includes index.
Keywords: Desert ecology -- Juvenile literature; Desert ecology; Ecology